Analisis Kewenangan Camat dalam Era Otonomi Daerah - Nabella Nabella (Journal of Education on Social Science (JESS), 2019)
This study aims to determine the authority of the Camat in the Era of Regional Autonomy in SitinjauLaut Subdistrict, Kerinci Regency and effects that hinder the implementation of the authority of the Camat in Sitinjau Laut District, Kerinci Regency.This research is motivated by a number of issues including the decline of functions, roles and authority of sub-district heads in government and sub-districts and sub-district heads. It is still seen as an important institution and actor whose role is in fostering social relations and public services. This research is descriptive with a qualitative approach. The informants of the study were determined purposively. Data is collected by making observations, interviews, and documentation studies and reduced so that conclusions can be drawn. The results showed that the delegation of authority was given based on the objectives and plans that had been prepared previously and the mechanism applied in SitinjauLaut Subdistrict had been based on the clarity of the position hierarchy even though the implementation was less effective due to the sub-district institution.